Physical exercise as a stress management mechanism - Stevanović, Tamara; Subotić, Slobodan; Milić, Marko Kimi (Medical Gazzette, 2026)
The way of reacting to potentially stressful situations is individual and depends on two basic factors. The first is the way a person perceives and interprets the situation, and the second factor relates to the state of the body itself, or the organism. Chronic stress, burnout syndrome and post-traumatic stress disorder often lead to the development of diseases. Stress can affect health directly, through the autonomic and endocrine reactions it causes, but also indirectly, through changes in health behavior that can occur due to stress. Physical exercise is often recommended as part of a stress management program. It has been proven that exercise reduces stress hormones and stress reactivity. Exercises adapted to the degree of physical capabilities and the levels of motivation of the person are considered an excellent initial approach to managing psychological stress. Physical activity is important not only as a primary prevention of many chronic diseases, but also as a secondary prevention that slows down and reduces the symptoms of chronic diseases. In addition to its impact on chronic diseases, physical activity also has a beneficial effect on improving self-confidence, social skills, cognitive functioning, and reducing symptoms of stress, which, together with other positive effects, contributes to a better quality of life. The results of existing research show that physical exercise can affect cognitive functioning throughout the lifespan directly, through physiological mechanisms and structural changes in the brain, and indirectly through its impact on mood and stress reduction. Physical exercise, through various mechanisms, has a strong impact on the manifestation of stress levels.